Empirical evidence and role mechanisms of big data enabling corporate green development - Yao Wang; Yitao Li; Zhen Ruan; Zihan Tang; Tilei Gao (Scientific Reports)
Abstract Driven by the growing challenges of global climate change and the urgent need to meet Sustainable Development Goals (SDGs), the green transformation of the economy has become a global consensus, with enterprises playing a crucial role. Using data from China’s A-share listed companies between 2010 and 2022, this paper examines the impact of big data advancements on corporate green development through the construction of a quasi-natural experiment. Specifically, the “National Big Data Comprehensive Pilot Zone” is used as a policy intervention to explore the causal effects of big data on corporate green practices. The findings indicate that the implementation of the big data pilot policy has fostered the adoption of more sustainable business practices, particularly in the eastern and central regions, as well as among large-scale enterprises. These positive effects are primarily driven by improved resource allocation and the reduction of agency costs. Based on these findings, the paper proposes a series of policy recommendations aimed at accelerating the green transition of the economy, offering valuable insights for policymakers and researchers.